2014
DOI: 10.2967/jnumed.114.137232
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT with 18F-FDG–Labeled Autologous Leukocytes for the Diagnosis of Infected Fluid Collections in Acute Pancreatitis

Abstract: Early detection of infection in acute pancreatitis (AP) affects the choice of treatment and clinical outcome. We used PET/CT with 18 F-FDGlabeled autologous leukocytes to detect infection in pancreatic or peripancreatic fluid collections in patients with AP. Methods: Fortyone patients (28 men and 13 women) who were 21-69 y old (mean ± SD, 41 ± 11.5) and had AP and radiologic evidence of a fluid collection in or around the pancreas were studied. Leukocytes were separated from the patient's venous blood, labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
0
32
0
4
Order By: Relevance
“…[5] 18 FDG therefore cannot distinguish bacterial infections from other pathologies such as cancer and inflammation, and cannot diagnose bacterial infections at an early stage. [5a, 6] Although numerous experimental PET contrast agents have been developed for imaging bacterial infections, such as radiolabeled antibiotics, [7] antimicrobial peptides, [1a] antibodies, [8] or white blood cells, [9] these agents have had minimal clinical impact. Several factors have contributed to the lack of success of bacteria imaging agents, such as poor clearance as a result of nonspecific adsorption, low target-receptor expression on bacteria, or complicated radiochemical synthesis, which are challenging to perform in clinical radiochemistry labs.…”
mentioning
confidence: 99%
“…[5] 18 FDG therefore cannot distinguish bacterial infections from other pathologies such as cancer and inflammation, and cannot diagnose bacterial infections at an early stage. [5a, 6] Although numerous experimental PET contrast agents have been developed for imaging bacterial infections, such as radiolabeled antibiotics, [7] antimicrobial peptides, [1a] antibodies, [8] or white blood cells, [9] these agents have had minimal clinical impact. Several factors have contributed to the lack of success of bacteria imaging agents, such as poor clearance as a result of nonspecific adsorption, low target-receptor expression on bacteria, or complicated radiochemical synthesis, which are challenging to perform in clinical radiochemistry labs.…”
mentioning
confidence: 99%
“…[4] However, 18 FDG is currently the only PET contrast agent available for clinical imaging of infections, and is problematic because it lacks specificity for bacteria and has a high uptake in mammalian cells. [5a, 6] Although numerous experimental PET contrast agents have been developed for imaging bacterial infections, such as radiolabeled antibiotics, [7] antimicrobial peptides, [1a] antibodies, [8] or white blood cells, [9] these agents have had minimal clinical impact. [5a, 6] Although numerous experimental PET contrast agents have been developed for imaging bacterial infections, such as radiolabeled antibiotics, [7] antimicrobial peptides, [1a] antibodies, [8] or white blood cells, [9] these agents have had minimal clinical impact.…”
mentioning
confidence: 99%
“…45 A recent study using PET/CT with fludeoxyglucose F 18 -labeled autologous leukocytes found increased tracer uptake in pancreatic fluid collections in 12 of 41 patients, among whom 10 had culture-proven infection with subsequent percutaneous drainage and 2 had unsuccessful aspirations. 50 In the same study, 29 patients with negative PET/CT scans had 25 proven negative cultures, and aspiration was unsuccessful in 4 cases. These results obtained with a noninvasive technique are promising but need to be confirmed in larger series.…”
Section: Superinfection Of Fluid Collectionsmentioning
confidence: 89%